The 2012 dengue outbreak in Madeira: exploring the origins - Wilder-Smith, Annelies (2014)
In 2012, Madeira reported its first major outbreak of dengue. To identify the origin of the imported dengue virus, we investigated the interconnectivity via air travel between dengue-endemic countries and Madeira, and compared available sequences against GenBank. There were 22,948 air travellers to Madeira in 2012, originating from twenty-nine dengue-endemic countries; 89.6% of these international travellers originated from Venezuela and Brazil. We developed an importation index that takes into account both travel volume and the extent of dengue incidence in the country of origin. Venezuela and Brazil had by far the highest importation indices compared with all other dengue-endemic countries. The importation index for Venezuela was twice as high as that for Brazil. When taking into account seasonality in the months preceding the onset of the Madeira outbreak, this index was even seven times higher for Venezuela than for Brazil during this time. Dengue sequencing shows that the virus responsible for the Madeira outbreak was most closely related to viruses circulating in Venezuela, Brazil and Columbia. Applying the importation index, Venezuela was identified as the most likely origin of importation of dengue virus via travellers to Madeira. We propose that the importation index is a new additional tool that can help to identify and anticipate the most probable country of origin for importation of dengue into currently non-endemic countries.